Thiol‐Click Based Polyglycerol Hydrogels as Biosensing Platform with In Situ Encapsulated Streptavidin Probes. Issue 1 (20th October 2022) - Thongrom, Boonya; Dimde, Mathias; Schedler, Uwe; Haag, Rainer
Abstract: An in situ streptavidin‐encapsulated hydrogel based on dendritic polyglycerol (dPG) which is functionalized with either an acrylate, allyl or acrylamide group and dithiolated polyethylene glycol (PEG) is constructed via a thiol‐click chemistry approach and is investigated for biosensing applications. The hydrogel platform is screened for the encapsulation and release efficiencies of the model protein streptavidin under varying physicochemical conditions, for example, crosslinking chemistry reactions, the molar ratio between the two gel components, macromonomer concentrations or pH‐values. By that, tailor‐made hydrogels can be developed, which are able to encapsulate or release the model protein for several days based on its modality. Furthermore, the accessible binding site of encapsulated streptavidin or in other words, the biotin‐binding performance is quantified, and the stability of the various hydrogel types is studied by rheology measurements, 1 H NMR, gel permeation chromatography (GPC), and mass loss experiments. Abstract : In situ streptavidin‐encapsulated hydrogels, which is fabricated from hyperbranched polyglycerol (dPG) and polyethylene glycol (PEG) by different types of thiol‐click reactions, show high elasticity, high encapsulation efficiency of 70% in average in all gel types and high biotin capacity. The results from release and degradation studies support an importance of linker chemistry for the different olefin acceptors.